Dynamic dependence between sectoral indexes of BRIC countries and the baltic dirty tanker index: An investigation using the generalized R2 approach - Şerife Akıncı Tok; Savaş Tarkun (Borsa Istanbul Review)
This study analyzes the dynamic connectedness between the Baltic Dirty Tanker Index (BDTI) and sector indexes in the stock exchanges of the BRIC countries, focusing on the chemical, oil, and raw materials sectors. Using daily data from January 1, 2015, to September 30, 2024, the analysis reveals significant pairwise relationships, highlighting the sensitivity of these sector indexes to shipping costs. The findings indicate that during periods of heightened market volatility, the BDTI has substantial influence, especially on Russia's chemical and India's oil and gas sectors. These results suggest that geopolitical risks and market uncertainty can significantly amplify interdependence. Based on these insights, proactive policies aimed at stabilizing shipping costs and improving cooperation among the BRIC countries are recommended to mitigate the impact of unexpected increases in freight rates. This study offers valuable information for policy makers, investors, and industry representatives for strengthening risk management strategies in shipping and logistics.